A comparison of "performance" during on-water racing and ergometer rowing - Ryan-Tanner, R.; Hahn, A.; Lawton, E.; Bellenger, S.; Kearns, A. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
If the 2000-metre ergometer test is a valid indicator of the physiological capacity for on-water racing, performance on the ergometer and on-water racing should be correlated. All major rowing races at International and National Competitions are contested over a distance of 2000 metres. The 2000-metre ergometer test involves the simulation of a race in controlled conditions where the rower is required to complete an amount of work equivalent to a distance of 2000 metres on the ergometer in the shortest possible time.